Earworm and event : music, daydreams, and other imaginary refrains - Priest, Eldritch (Thought in the act., 2022)
"Eldritch Priest questions the nature of sound, music, thought, and affect by analyzing the phenomenon of the earworm: those reveries that hijack our attention, the shivers that run down our spines, and the songs that stick in our heads."--